2006
DOI: 10.1186/1476-511x-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Shift working and risk of lipid disorders: A cross-sectional study

Abstract: Background: previous studies have indicated on association between shift work and lipid profile disturbances. Lipid profile disturbances could be due to internal desynchronization. The aim of this study was to analyze whether there is relationship between shift work and serum lipids, fasting blood glucose and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 14 publications
12
39
1
Order By: Relevance
“…However, Atkinson et al 2 posit that these results are not entirely consistent on which non-specifi c lipid concentrations are altered. Ha and Park 11 and Biggi 3 also found that shift-workers have higher cholesterol levels than dayshift workers, whereas Ghiasvand et al 7 found elevated levels of LDL-cholesterol. Irregular-shift workers are at increased risk of developing cardiovascular diseases compared to day-shift workers.…”
Section: Discussionmentioning
confidence: 98%
“…However, Atkinson et al 2 posit that these results are not entirely consistent on which non-specifi c lipid concentrations are altered. Ha and Park 11 and Biggi 3 also found that shift-workers have higher cholesterol levels than dayshift workers, whereas Ghiasvand et al 7 found elevated levels of LDL-cholesterol. Irregular-shift workers are at increased risk of developing cardiovascular diseases compared to day-shift workers.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of shift work on body weight has been investigated in previous studies, several of which demonstrated a significant tendency to become overweight [6,27,28]. In contrast, some studies failed to show such associations [15,29].…”
Section: Discussionmentioning
confidence: 98%
“…Shift work was defined as work at times out of normal daylight hours 8:00 am to 2:00 pm or work during the weekends [15]. An additional question representing the shift work period was asked.…”
Section: Study Design and Samplementioning
confidence: 99%
“…Several of them have demonstrated a significant relation between working in shifts and body weight or obesity (26)(27)(28)(29), while some others did not (30,31). Most of these studies, however, had a crosssectional design and thereby failed to determine a clear causal relationship between shift work and body weight change.…”
mentioning
confidence: 99%
“…In recent years, several studies have investigated the association between shift work and weight gain, overweight, or obesity (26)(27)(28)(29)(30)(31). Several of them have demonstrated a significant relation between working in shifts and body weight or obesity (26)(27)(28)(29), while some others did not (30,31).…”
mentioning
confidence: 99%